Isolation and Identification of Enterococcus spp. Resistant to Macrolides Antibiotics - Molan, Nabaa Kamil; Hussien, Alyaa Razooqi (Iraqi Journal of Science, 2024)
Gram-positive enterococciare opportunistic and resistant to many antibiotics. This study aimed to investigate the presence of Enterococcus spp. in our community and whether these isolates are resistant to the macrolides class of antibiotics. Fifty isolates from 112 clinical samples were recognized as Enterococcus spp. and confirmed using Vitek-2 system. The current study found that 50/112 (44.6%) represented the total isolates, 38/50 (76%) of which were Enterococcus faecalis, while 12/50 (24%) were Enterococcus faecium, twenty (40%) isolates from root canals and 30 (60%) isolates from urine were isolated. The sensitivity of the enterococcal isolates to various macrolides (erythromycin, azithromycin and clarithromycin) antibiotics was determined by using the disk diffusion approach. Later, the minimum inhibitory concentrations (MICs) for erythromycin and the most resistant drug among this group  were investigated using the agar dilution technique. And then molecular detection for mef gene was done using two specific primers via PCR technique. The current findings revealed high resistance rates to macrolide antibiotics which were reported in 21/50 (42%) of total isolates and at significant levels of MIC values for most isolates (57%). And as for the PCR results, it was negative for mef gene in all tested isolates.